Manajemen Kegiatan Ekstrakurikuler SD Negeri Pergiwatu Kabupaten Kulon Progo - Rahmat Mulyono; Agnestia Medelin Rambu Ata Ratu; Indah Fuji Mahesa; Melody Mayang Cendana (Manajer Pendididikan, 2023)
This study aims to analyze the management of extracurricular activities, especially drumband at SD Negeri Pergiwatu, which consists of the stages of planning, organizing, implementing, and supervising. This study uses a qualitative research stage method. Based on the research results obtained, the planning of drum band extracurricular activities is carried out through coordination meetings involving school principals, school committees, drumband extracurricular teachers, extracurricular assistant drumband teachers and class teachers. Organizing is done by forming an extracurricular activity team. Activities are carried out by utilizing available infrastructure and monitoring of drumband extracurricular activities is carried out by a supervisory team in monitoring the course of activities so that they can run according to the objectives in planning.